2001
DOI: 10.1007/bf02825878
|View full text |Cite
|
Sign up to set email alerts
|

OR-1—a mixture of esters of glyceric acid produced byPenicillium funiculosum and its antitrypsin activity

Abstract: A mixture of related metabolites (denoted OR-1) was isolated from the fermentation broth of Penicillium funiculosum together with mitorubrinic acid. Structurally OR-1 is glyceric acid esterified with C14-C18 fatty acids. Steady-state studies revealed that OR-1 behaved like an uncompetitive trypsin inhibitor with Ki 17.6 mumol/L.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 9 publications
0
17
0
Order By: Relevance
“…Previously, a mixture of GA esters biochemically produced by Penicillium funiculosum was reported to exhibit antitrypsin activity 15 . We reported that chemically synthesized dioleoyl GAs also exhibit antitrypsin activity 13 .…”
Section: Introductionmentioning
confidence: 99%
“…Previously, a mixture of GA esters biochemically produced by Penicillium funiculosum was reported to exhibit antitrypsin activity 15 . We reported that chemically synthesized dioleoyl GAs also exhibit antitrypsin activity 13 .…”
Section: Introductionmentioning
confidence: 99%
“…However, this value differs from the IC 50 of OR-1, which is 4.25 μM 13 . The analytical data on the structure of OR-1 13 suggest several structural possibilities, including GA diesterifi ed with homologous or heterologous fatty acids, and a mixture of 2-O-monoacyl-GA and 3-O-monoacyl-GA with homologous or heterologous fatty acids. However, the contributions of these possible OR-1 constituents to the antitrypsin activity are unknown.…”
Section: Synthesis Of Dioleoyl D-glyceric Acid and Dioleoyl L-glycerimentioning
confidence: 59%
“…However, because only 100 mg of OR-1 was prepared from a 5-L culture of P. funiculosum 13 in one study, its productivity appears to be low. Additionally, OR-1 was revealed to be only a mixture of esters of GA, and, from the published data 13 , it remains unknown whether it is diacyl-GA, a mixture of 2-O-monoacyl-GA and 3-O-monoacyl-GA, or their mixture.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations